The Effect of ZJXG Decoction on The Serum Level of Growth Hormone and The Expression of GH Receptor in Callus - Zhou, Zhen; Wang, Guanxi; Liu, Zhaogang; Guo, Yunliang (JOURNAL OF ADVANCES IN BIOLOGY, 2019)
The aim of experiment was to investigate the effects of Zhuangjin XuGu decoction (ZJXG decoction) on growth hormone (GH) serum and GH receptor (GHR) expression in callus. The femur fracture animal models were generated in 72 Wistar rats by cutting femur transversely at the middle point. The rats models were administered orally ZJXG decoction for 28 days. Anatomy, X-ray and hematoxylin- eosin (HE) staining were used to observe the healing process in rats. The expression of growth hormone receptor (GHR) in fibroblasts and osteoblasts in callus was evaluated by immunohistochemical assay (IHC). The serum level of GH was passed by enzyme linked immunosorbent assay (ELISA). Anatomy, X-ray and H-E staining indicated that the fibrous callus at the fracture-end increased and the fibrous granular tissue changed gradually to fibrous, cartilaginous and osseous callus. IHC and ELISA showed that after 28 days of ZJXG Decoction treatment, that GH in the fibroblasts and osteoblasts of callus and their serum level increased significantly. These results suggested that ZJXG decoction could enhance the fracture healing by enhancing GH activity and promoting the expression of GHR in the fibroblasts and osteoblasts of callus in rats.